Human-driven global nutrient imbalances increase risks to health - Penuelas, Josep; Sardans, Jordi (Eco-Environment & Health, 2023)
Human-induced inputs of nitrogen (N) and phosphorus (P) into the biosphere have reached unprecedented levels, particularly N, leading to an escalating global anthropogenic N:P ratio. This ratio has emerged as a significant driver of environmental change, impacting organisms, ecosystems, and global food security. However, the implications of this ratio for human health have been largely overlooked and remain uncertain. This article aims to fill this knowledge gap by exploring the potential effects of N:P ratios on both non-infectious and infectious diseases. Preliminary data emphasize the importance of investigating the influence of N:P ratios on human health, suggesting a potential role in the rise of non-infectious diseases, such as cancer, as well as the proliferation of infectious diseases, including Zika and malaria. These findings highlight the urgent need for increased attention from the scientific community and policymakers regarding the complex impacts of the human-induced biospheric N:P ratio. It is crucial to investigate and understand the underlying mechanisms and drivers behind these effects. Furthermore, there is significant potential for improving human health through the manipulation of N:P ratios and the availability of N and P. This applies not only to medical treatments but also to innovative fertilizer management strategies. These avenues present promising opportunities to address the challenges associated with human health in an ever-changing world. [Display omitted] •Unprecedented N:P ratio impacts environment, organisms, food security.•N:P ratios may affect non-infectious and infectious diseases.•Urgent need to study N:P ratio effects on human health.•Potential for improving health through N:P manipulation.•N:P ratios offer opportunities for addressing health challenges.